Extremism prevention and political ”Bildung” On the increase in extremism-preventive approaches and their effects on political „Bildung” - Haselwanter, Martin (Momentum Quarterly, 2023)
Since the mid-2010s, there have been increasing efforts in Austria to counter developments that have been identified as radical or extremist by means of extremism prevention. Political „Bildung” seems to be losing importance in this field. The central thesis of this article is that a creeping marginalisation of „Bildung” is taking place due to an increase in preventive approaches. What is the reason for this and what effects does the increase in extremism-preventive approaches have on political „Bildung”? One possible answer is sought in the action logical differences between prevention and (political) „Bildung”.
Keywords: Prevention of extremism; political “Bildung"; civic education; marginalisation of “Bildung”